BIOBANKS ARE AN ESSENTIAL TOOL FOR TRANSPLANTATION. HISTORY, CURRENT STATE, PERSPECTIVES - O. N. Reznik; D. O. Kuzmin; A. E. Skvortsov; A. O. Reznik (Вестник трансплантологии и искусственных органов, 2017)
Organ shortage remains to be a crucial issue in transplantation. However, it’s not the only challenge that modern transplantation is facing. There are critical issues to be solved, such as, choosing optimal patient-specific immunosuppressive regimen, preventing or coping effectively with graft rejection and improving graft and patient survival rates. There are still a number of ongoing studies on ischemia-reperfusion injury mechanisms. It is also unknown what the true limitations of organ viability are and what mechanisms actually regulate it. The upcoming era of personalized medicine dictates the necessity for individualized approach to these issues. The creation of transplant biobanks followed by different studies on their base may be the key option to resolve problems of modern transplantation. Biobanks are an essential basis of personalized medicine, which allows largescale population studies, discovery of new biomarkers and therapy targets as well as new drugs development. The importance of this relatively new fi eld has increased over last decades making its way from small collections of samples to large national and international biorepositories. There are biobanks of different types and purposes. In this article a systematic review is given covering historical reference, term definition, and classifi cation variants. Furthermore, the current state of the industry is highlighted along with current issues and perspectives with respect to transplantation.